Prediction of the initial point of the last cycle in undrained cyclic triaxial tests on flow liquefaction. Issue 120 (May 2019) - Ye, Bin; Ni, Xueqian; Ye, Guanlin; Huang, Yu; Lu, Ping
Abstract: Flow liquefaction will cause the sudden failure of loose sand specimens when they are subjected to stress-controlled cyclic loading in undrained triaxial tests, and thus few data points can be obtained during this process. To overcome this problem and conduct a detailed investigation of the flow liquefaction behaviours, a two-staged loading method was proposed, in which stress-controlled cyclic loading was switched to strain-controlled monotonic loading after reaching the initial point of the last cycle (IPLC) in undrained cyclic triaxial tests on flow liquefaction. The characteristics of the IPLC were first investigated through a series of undrained triaxial tests, and then a linear relationship between the excess pore water pressure (EPWP) ratio at the IPLC and the cyclic stress ratio ( CSR ) was obtained for predicting the location of the IPLC. The verification testing results proved that the relationship can predict the IPLC accurately, which makes it possible to switch the loading mode at the right point and make a detailed investigation of the flow liquefaction behaviours of loose sand. Highlights: A loading method was proposed to overcome the sudden failure of sand due to flow liquefaction. A criterion was found to determine the failure mode of flow liquefaction. A simple method was proposed for predicting the initial point of flow liquefaction.